The Evidence Theory and Methodology of Axiological Completions in the Context of Philological Training - Botezatu, Liuba (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
The first step of evidencing the axiological completions occurs, in our int erpretation, at the level of Retroaction in the context of linguistic and literary education as right as a modern teaching technology in the cu rricular pre-university system. The second stage (bachelor-master), of completing evidence, in perfect ascension (of the same interpretation L.B.) occurs at co-reporting level: Principle of Global Axiology - Methodology of Evidencing the Axiological Completions engagement on a new level of becoming: training the philologist teacher. Happiness lies in to know yourself: the stylistic matrix of the biased nation, the mother language the language of raw ascensions into the great spirituality; the own possibilities of opening manifestation of self-realization in the universal circuit. Or, this is the primary purpose of participating approaches / engagements in professional plan: training / forming the philologist philological genetic (bilingual multi-lingual), philological centrist by vocation.The joints of the Evidence Methodology of Axiological Completions / MECA in this structural-phenomenal context are, on the one hand, those relating to translation into life of the possibilities / requirements listed, taking preponderance here: the possibility of returning to essence the ability of ascension through spirituality - the possibility of highlighting the axiological completions, on the other hand - those related to the focus on diversification - information - unification, on the establishment of syntactical highlight of the pertinent datum.